2014
DOI: 10.1007/s00425-014-2159-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome re-sequencing suggested a weedy rice origin from domesticated indica-japonica hybridization: a case study from southern China

Abstract: Whole-genome re-sequencing of weedy rice from southern China reveals that weedy rice can originate from hybridization of domesticated indica and japonica rice. Weedy rice (Oryza sativa f. spontanea Rosh.), which harbors phenotypes of both wild and domesticated rice, has become one of the most notorious weeds in rice fields worldwide. While its formation is poorly understood, massive amounts of rice genomic data may provide new insights into this issue. In this study, we determined genomes of three weedy rice s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 46 publications
8
55
0
1
Order By: Relevance
“…According to De-Wet and Harlan (1975), weedy rice originated from the selection and adaptation of wild rice to agricultural habitats. In regions where no wild rice has been grown, weedy rice may instead originate from cultivated rice through de-domestication with adaptive mutations and the accumulation of beneficial mutants (Ishikawa et al 2005;Cao et al 2006;Reagon et al 2011;Thurber et al 2010;He et al 2014;Qiu et al 2014;Lu et al 2016;Li et al 2017;Qiu et al 2017). In the case of Brazil and Italy, where no wild Oryza types are indigenous, contamination of seed stocks with wild Oryza species has been proposed as a source of weedy rice (Carney 2004;Grimm 2014).…”
Section: Origin and Evolutionmentioning
confidence: 99%
“…According to De-Wet and Harlan (1975), weedy rice originated from the selection and adaptation of wild rice to agricultural habitats. In regions where no wild rice has been grown, weedy rice may instead originate from cultivated rice through de-domestication with adaptive mutations and the accumulation of beneficial mutants (Ishikawa et al 2005;Cao et al 2006;Reagon et al 2011;Thurber et al 2010;He et al 2014;Qiu et al 2014;Lu et al 2016;Li et al 2017;Qiu et al 2017). In the case of Brazil and Italy, where no wild Oryza types are indigenous, contamination of seed stocks with wild Oryza species has been proposed as a source of weedy rice (Carney 2004;Grimm 2014).…”
Section: Origin and Evolutionmentioning
confidence: 99%
“…Although multiple origins for weedy rice have been proposed, currently de-domestication from cultivated varieties has been acknowledged as one of the main routes for the origin of weedy rice all over the world891011121314. This kind of weed is also one of the plants identified by Ellstrand et al 3.…”
mentioning
confidence: 99%
“…Several previous studies have provided helpful insights into this process910111213141921. For instance, Reagon et al 19.…”
mentioning
confidence: 99%
“…), harbors characteristics of undomesticated Oryza species, including seed dispersal mechanisms and seed dormancy. It also possesses traits of domesticated rice, such as rapid growth, and resembles domesticated rice during the seedling stage, which promotes its invasiveness in the agroecosystem2627. The origin of weedy rice has long been discussed, which has led to several hypotheses, including the ongoing selection and adaptation of wild rice2829, hybridization between cultivated rice and its progenitor type30, hybridization between indica - japonica 26, ongoing and multidirectional hybridization between weedy rice and cultivated types, and among weedy types31.…”
mentioning
confidence: 99%
“…It also possesses traits of domesticated rice, such as rapid growth, and resembles domesticated rice during the seedling stage, which promotes its invasiveness in the agroecosystem2627. The origin of weedy rice has long been discussed, which has led to several hypotheses, including the ongoing selection and adaptation of wild rice2829, hybridization between cultivated rice and its progenitor type30, hybridization between indica - japonica 26, ongoing and multidirectional hybridization between weedy rice and cultivated types, and among weedy types31. Simple sequence repeats based analyses of the genetic diversity of weedy rice populations from China suggested that weedy rice most likely originated from local indica or japonica varieties2732.…”
mentioning
confidence: 99%